1595. Impact of Levofloxacin for the Prophylaxis of Bloodstream Infection on the Gut Microbiome in Patients with Hematologic Malignancy. (26th November 2018) - Ziegler, Matthew; Han, Jennifer H; Landsburg, Daniel; Pegues, David; Reesey, Emily; Gilmar, Cheryl; Gorman, Theresa; Bink, Kristen; Moore, Amy; Kelly, Brendan J; ,
Abstract: Background: Prophylactic antibiotics for the prevention of bloodstream infections (BSIs) during neutropenia (NTP) may reduce the incidence of BSIs, NTP fever, and mortality. However, antibiotics may also result in dysbiosis of the gut microbiome. We aimed to study the impact of levofloxacin prophylaxis compared with broad-spectrum β-lactam (BSBL) antibiotics used for the treatment of NTP fever on gut microbiome features in patients with hematologic malignancy. Methods: Stool specimens from hematologic malignancy patients admitted for chemotherapy or stem cell transplant (SCT) in the setting of the evaluation of diarrhea were collected from September 2017 to November 2017. Levofloxacin prophylaxis was standard of care for patients undergoing autologous SCT or induction chemotherapy for acute myeloid leukemia (AML). 16S rRNA (V1–V2 amplicon) sequencing was performed using the Illumina HiSeq platform, formation of operational taxonomic units (OTUs) was performed using QIIME 1.9.1, and taxonomic assignment was performed via the GreenGenes database (13.8). Descriptive statistics were used to compare microbiome features. Results: A total of 57 samples from 44 patients were included, most with AML (42%), multiple myeloma (33%), or non-Hodgkin's lymphoma (12%). In the 7 days prior to sample collection, 28 (49%) patients received a BSBL and 17 (29%) received levofloxacin. The gut microbiome of patients with BSBL exposure had significantly reduced Shannon alpha diversity compared with those without: median 1.96 (IQR 1.08–2.57) vs. 2.58 (IQR 2.05–2.93); P < 0.01. However, those with and without levofloxacin exposure showed no difference: median 2.37 (IQR 2.19–2.75) vs. 2.22 (IQR 1.71–2.81), respectively; P = 0.48. Additionally, those with BSBL exposure trended toward increased dominance with non-Bacteroidetes taxa: 14 (60%) vs. 14 (41%); P = 0.14. In contrast, levofloxacin exposure was associated with a lower risk of dominance: 2 (8%) vs. 15 (55%); P < 0.01 and was associated with a greater proportion of Bacteroidetes taxa: 75% vs. 27% ( P < 0.01). Conclusion: Our findings suggest that the impact of antibiotics on the gut microbiome vary by class, and that levofloxacin may have limited impact on the gut microbiome in this patient population. Further studies are needed to investigate this potential differential impact of antibiotic classes. Disclosures: D. Pegues, DaVita / Total Renal Care: Consultant, Consulting fee.